Energy information flow-based ecological risk transmission among communities within the heavy metals contaminated soil system. (January 2022) - Peng, He; Chen, Yizhong; Li, Jing; Lu, Jingzhao
Abstract: An energy information flow-based ecological risk assessment framework (EIF-ERA) is developed for identifying ecological risk transmission rules among communities (i.e., vegetation E1, herbivorous animals E2, soil microorganisms E3, and carnivorous animals E4) within the heavy metals contaminated soil system. This framework is integrated with numerous techniques of carcinogenic risk evaluation, ecological risk assessment (ERA), and Monte Carlo simulation. Stepwise quadratic response surface analysis (SQRSA) is employed for reflecting the relation between contaminants' concentration and comprehensive risk. Two scenarios with respect to the environmental quality standards (scenarios 1) and carcinogenic risk reversion (scenarios 2) are merged into the EIF-ERA. A real-world mining area in Xinglong County in Chengde is selected to verify the developed framework's effectiveness. Results reveal that E3 is considered as the most sensitive community when contaminant interference occurs, and its 62.3% and 37.7% of comprehensive risk are contributed by initial and direct risks, respectively. Other communities can receive direct risk through control allocation (CA). Monte Carlo anlysis shows that there are 7.68% and 20.25% increase in the initial risk of Cd and Pb when their quantile statistics increase from 70% to 90%. Determination of an appropriate screening value is vital for contaminated mining soil remediation due to its inefficiency of remediation funds, especially when considering the trict standards of contaminants' concentration within scenarios 1. The surrogates obtained from the SQRSA display the relation of contaminant concentration and comprehensive risks with the adjusted R 2 greater than 0.77. These findings can be in support of system design, risk assessment, and site remediation. Graphical abstract: Image 1 Highlights: EIF-ERA is developed for identifying ecological risk transmission rules among communities. Two scenarios can guide the selection of appropriate remediation standard based on screening value. SQRSA can reflect the relation between contaminants concentration and comprehensive risks. Findings can support system design, risk assessment, and site remediation.